Research progress of Traditional Chinese Medicine life nurturing in health management of patients with type 2 diabetes mellitus (中医养生理论在2型糖尿病患者健康管理中的应用研究进展) - CHEN Yao (陈瑶); BU Weiqin (卜炜琴) (中西医结合护理)
The development of diabetes mellitus is highly associated with the poor lifestyle habits. The Traditional Chinese Medicine life nurturing plays a crucial role in prevention and control of diabetes mellitus. In perspectives of emotion, dietary, exercise and routine management, this paper summarized the application of Traditional Chinese Medicine life nurturing in health management of patients with type 2 diabetes mellitus, and provide reference for further research on health management of patients with type 2 diabetes mellitus. (糖尿病的发生发展与生活方式有着密不可分的关系, 中医养生在防治糖尿病方面发挥了重要作用。本研究就中医养生理论在2型糖尿病患者情志护理、饮食护理、运动护理以及常规护理方面的应用现状进行综述, 旨在为今后中医养生理论在2型糖尿病患者健康管理中的进一步深入研究提供参考。)